Development of digital learning evaluation In realizing Suistainable Development Goals (SDGs) - Sudi Dul Aji; Hestiningtyas Yuli Pratiwi; Arief Rahman Hakim; Muhammad Nur Hudha; Nada Damai Azka (Universitas Kanjuruhan Malang, 2023)
This research is motivated by one of the goals of the SDGs, namely realizing quality learning and handling environmental change. The purpose of this study is to determine the feasibility and practicality of evaluating digital learning in realizing the SDGs for elementary school students. This research is a development research with the ADDIE model (Analysis, design, development, implementation and evaluation). The test subjects in this study were class VI students at SDN 02 Putatkidul Gondanglegi. The data collection instrument uses a questionnaire. Data analysis techniques use quantitative data. Digital Study Evaluation created using the Kahoot! based on the results of the material validation, a score of 93.75% was obtained in the very feasible category, the results of the language validation were 95% (very feasible), the results of the teacher's practicality validation were 88.8% (very practical) , the students' practicality results were 94% (very practical)